Jurnalisme Islam Dalam Persefektif Al Qur’an Surat Al Alaq 1-5 - Muhamad Bisri Mustofa; Gesti Cania; Siti Wuryan (STAI Bumi Silampari, 2022)
This study aims to describe the Implementation of the Koran Surah al-'Alaq verses 1-5 in Islamic journalism . Contained in Surah al-alaq 1-5. On these dates, Surah al-Arak 1-5 comes from the Qur'an, and several experts from Al-Malagi, Ibn Katzir, Al-Misbah, and Al-Mizan. The data used were the Talley method and the content analysis method. The results of this study show that the concept of learner/learning in Sura al alaq is interpreted in terms of intellectual enlightenment. This becomes a habit of further study/application thereof, as can be seen from his double repetition of the word iqra. When it comes to learning/reading on iqra, you don't just read the text here, you naturally read the situation as well.